(untitled) (Global Journals of Research in Engineering, 2012)
Municipal Solid Waste (MSW) is defined to include refuse from households, waste from commercial establishments, and refuse from institutions, market waste, yard waste and street sweeping (World Bank 1994). Waste is an unavoidable by-product of human activities, economic development, urbanization and improving living standards in cities. The increase in quantity and complexity of waste generated in municipalities and notified areas have become serious concern for Government departments, pollution control agencies, regulatory bodies and also the public in India. Inefficient management, utilisation and disposal of this solid waste is an obvious cause for the degradation of environment in India. Improper disposal of this waste generated leads to spread of communicable diseases, causes obnoxious conditions, pollutes all vital components of living environment (air, water